The Effect of Social Support and Emotional Intelligence on Culture Shock of the Newcomer Students: the Mediating Role of Resilience - Eka Putra; Eko Sujadi; Yuserizal Bustami; Syaiful Indra (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2022)
Culture shock is one of the main problems for newcomer students. Some factors influencing culture shock include social support, emotional intelligence, and resilience. This study aimed to investigate the direct effect of social support and emotional intelligence on culture shock and indirectly through resilience. 85 newcomer students participated in the sudy filling the Culture Shock Questionnaire developed by Mumford in 1998, the Multidimensional Scale of Perceived Social Support developed by Zimmet et al in 1988, The Brief Resilience Scale by Smith in 2008, and Emotional Intelligence Questionnaire developed by Victor Dulewicz & Malcolm Higgs in 1999. The data were analyzed by using SmartPLS 3.0. The result of the study showed that social support and emotional intelligence influenced culture shock significantly. Also, the result showed that resilience had a mediation effect on those relationships. The institution or university needs to create a learning environment which facilitate diversity. Thus, guidance and counseling services should be utilized to avoid and overcome the culture shock problem.